2023
DOI: 10.3389/feart.2022.1085327
|View full text |Cite
|
Sign up to set email alerts
|

Construction applicability of mechanical methods for connecting aisle in the bohai mudstone stratum with high water pressure

Abstract: China’s traditional connecting aisle construction technology is mainly to combine soil reinforcement with mining excavation. The technology is relatively mature, but it has shortcomings such as long construction period and long-term construction settlement. In order to overcome the above shortcomings, mechanical methods for connecting aisle technology has become increasingly mature after years of research and development, and has been successfully applied in many areas. For the cross-sea tunnel project, this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Meanwhile, other experts studied the security issue of mechanical connection channels under train loads and seismic loads using the finite element method and concluded that joints are prone to fatigue damage under dynamic loads [11,12]. Zhang et al [13,14] took the practical application of a mechanical contact channel in a coastal area as the background, evaluated the construction safety, and verified the applicability of mechanical contact channel construction in a highwater-pressure mudstone stratum by numerical simulation. In recent years, it has been found in engineering practice that steel-ring secondary lining composite segments should be used at connecting positions to ensure a good seal between the contact channel and the main tunnel, but its deformation law in the cutting process has not been extensively studied yet [15].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, other experts studied the security issue of mechanical connection channels under train loads and seismic loads using the finite element method and concluded that joints are prone to fatigue damage under dynamic loads [11,12]. Zhang et al [13,14] took the practical application of a mechanical contact channel in a coastal area as the background, evaluated the construction safety, and verified the applicability of mechanical contact channel construction in a highwater-pressure mudstone stratum by numerical simulation. In recent years, it has been found in engineering practice that steel-ring secondary lining composite segments should be used at connecting positions to ensure a good seal between the contact channel and the main tunnel, but its deformation law in the cutting process has not been extensively studied yet [15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, based on the working environment of the Gaojiapu Coal Mine in the Zhengtong Coal Industry of Shaanxi Province, this paper will study the technical improvement of the open TBM system and supporting equipment so that the open TBM can better adapt to the environment of the Gaojiapu Coal Mine excavation face and improve the efficiency of excavation work. In addition, the open TBM construction causes less disturbance to the surrounding rock and can form a neat roadway section, which is conducive to the future use of underground mine empty areas to build oil and gas storage (Qiu et al, 2023) (Zhang et al, 2023) (Qiu et al, 2022) (Fan et al, 2016) (Wang et al, 2023) (Chen et al, 2020) (Zhao et al, 2023) (Fan et al, 2020c). Finally, by comparing the excavation workload generated by different excavation construction techniques in the Gaojiapu Coal Mine, the advantages of using the improved open TBM are objectively evaluated.…”
Section: Introductionmentioning
confidence: 99%